2016
DOI: 10.5144/0256-4947.2016.356
|View full text |Cite
|
Sign up to set email alerts
|

The impact of renal angiomyolipoma on estimated glomerular filtration rate in patients with tuberous sclerosis complex

Abstract: BACKGROUNDThere is a growing concern that renal impairment may develop in patients with renal angiomyolipomas (AMLs) associated with tuberous sclerosis complex (TSC) as a consequence of the disease itself and/or the interventions to mitigate the risk of hemorrhage.OBJECTIVETo assess the estimated glomerular filtration rate (eGFR) in patients with bilateral renal AMLs and the impact of tumor burden and intervention on renal function.DESIGNRetrospective study.SETTINGUrology department of a tertiary care hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
(35 reference statements)
1
4
1
Order By: Relevance
“…In our study, the prevalence of angiomyolipoma was significantly higher in those with TSC2 mutations. This was in line with the previous other reports (7,8,17,23). We also observed that patients with TSC2 mutations had angiomyolipoma at early age and experienced higher rates of bleeding complications (haematuria and hemorrhage).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the prevalence of angiomyolipoma was significantly higher in those with TSC2 mutations. This was in line with the previous other reports (7,8,17,23). We also observed that patients with TSC2 mutations had angiomyolipoma at early age and experienced higher rates of bleeding complications (haematuria and hemorrhage).…”
Section: Discussionsupporting
confidence: 93%
“…In our previous publication from the TOSCA core section interim analysis ( 13 ), we reported that the occurrence rate of renal angiomyolipomas was lower in the TOSCA cohort compared to other published literature ( 8 , 9 ). Rates of haematuria and hypertension were also lower compared with those reported in TSC patients in other studies ( 6 , 7 , 21 , 22 ), this may be a reflection of the age relatively young age of our subjects and possibly under-ascertainment. These lower rates of occurrence of renal angiomyolipomas and angiomyolipoma-related complications could be explained by a different (younger) age range of our population; however the current analysis shows that angiomyolipoma prevalence rose progressively with age, to 77.7% in those over 40 years of age, whereas complication rates remained much lower than in other studies.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Because AML has a highly vascular tissue, repeated embolisation procedures may lead to rapid kidney function decline through ischaemic acute tubular necrosis. 3 Acute kidney injury (AKI) post embolisation can be due to contrast related AKI, vascular compromise of nephrons due to coiling of vessels, inflammation caused due to embolisation agents, formation of haematoma, perioperative haemodynamic instability and atheroembolic phenomenon.…”
Section: Descriptionmentioning
confidence: 99%
“…Some reports indicated that intervention was not associated with renal impairment, while others showed that inter vention/surgery rather than the AML lesions was associated with deterioration of renal function ( 119 , 120 ). The discrepancy may be related to the relative proportions of sporadic versus TSC-RAML, where most of the reports associating renal impairment with RAML involve TSC patients.…”
Section: Renal Impairmentmentioning
confidence: 99%